2020
DOI: 10.1128/iai.00474-20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Myeloid Hif-1β Deletion on the Intestinal Microbiota in Mice under Environmental Hypoxia

Abstract: External environmental factors can cause an imbalance in intestinal flora. For people living in the extremes of a plateau climate, lack of oxygen is a primary health challenge that leads to a series of reactions. We wondered how intestinal microorganisms might change in a simulated plateau environment, and what changes might occur in the host organism and intestinal microorganisms in the absence of hypoxia-related factors. In this study, mice carrying a knockout of hypoxia-inducible factor 1β (Hif-1β) in myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…During environmental hypoxia in mice, the Bacteroidetes abundance increased at both the family and genus levels from days 1 to 14 in mice with hypoxia inducible factor-1 (HIF-1) deficiency in their bone marrow cells. This difference was significant compared with that of the wild-type group ( Han N. et al, 2020 ) and was consistent with previous findings that Bacteroidetes was more abundant in HIF-1-deficient mice than in wild-type mice ( Sun et al, 2020 ).…”
Section: Altitude-associated Hypoxia and The Gut Microbiotasupporting
confidence: 92%
“…During environmental hypoxia in mice, the Bacteroidetes abundance increased at both the family and genus levels from days 1 to 14 in mice with hypoxia inducible factor-1 (HIF-1) deficiency in their bone marrow cells. This difference was significant compared with that of the wild-type group ( Han N. et al, 2020 ) and was consistent with previous findings that Bacteroidetes was more abundant in HIF-1-deficient mice than in wild-type mice ( Sun et al, 2020 ).…”
Section: Altitude-associated Hypoxia and The Gut Microbiotasupporting
confidence: 92%
“…In humans, the levels of HIF-1 transcripts are directly correlated with those of hypothalamic transcripts for proteins involved in inflammation, regulation of apoptosis, autophagy, and the ubiquitin/proteasome system; in mice with high fat diet, diet-induced obesity was accompanied by increased HIF-1 expression ( 52 ). Moreover, mice carrying the myeloid HIF-1β deletion displayed aggravated hypoxic phenotypes and significantly greater weight loss and significantly higher cardiac index values than the wild-type group ( 53 ). Considering that platelet thrombus formation is usually positively correlated with hyperlipidemia, the increase of HIF-1β might indicate the accumulated inflammation and the disorder of lipid metabolism in CE stroke.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, we are not aware of other studies investigating an impact of MDSC on intestinal microbiome composition. However, it has been shown that a myeloid knockout of HIF‐1β leads to altered microbiome composition in mice exposed to hypoxia [59]. Conversely, metabolites produced by the intestinal microbiome were shown to influence the expression of HIF‐1α; for example, short chain fatty acids (SCFA) cause HIF‐α stabilization by inhibition of prolylhydroxylases (PHDs) [60].…”
Section: Discussionmentioning
confidence: 99%